2019
DOI: 10.12944/crnfsj.7.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Hazelnuts as Source of Bioactive Compounds and Health Value Underestimated Food

Abstract: Hazelnut (HN) has found its way into nontraditional foods due to the recognition of its nutritional and nutraceutical properties. Among nut species, hazelnut plays a major role in human nutrition and health because of its special composition of fat (mainly oleic acid), dietary fibre, vitamins (vitamin E), minerals, phytosterols (mainly β-sitosterol), and antioxidant phenolics. In particular, lipids represent 60% of its dry weight and are mainly represented by triacylglycerols where the main fatty acids are ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 96 publications
0
21
0
Order By: Relevance
“…Among lipids, the monounsaturated fatty acids (MUFAs) are the major group of hazelnut oil due to the high amount of oleic acid (70‐85%), with the total polyunsaturated fatty acids (PUFAs) and total saturated fatty acids (SFAs) in a low amount 19, 99 . Furthermore, research 134 has reported that the total lipids consisted of 98.8% triacylglycerols and 1.2% polar lipids. Nuts are cholesterol‐free, but their fatty fraction contains sizeable amounts of chemically related non‐cholesterol sterols, belonging to a heterogeneous group of compounds known as plant sterols or phytosterols.…”
Section: Introductionmentioning
confidence: 99%
“…Among lipids, the monounsaturated fatty acids (MUFAs) are the major group of hazelnut oil due to the high amount of oleic acid (70‐85%), with the total polyunsaturated fatty acids (PUFAs) and total saturated fatty acids (SFAs) in a low amount 19, 99 . Furthermore, research 134 has reported that the total lipids consisted of 98.8% triacylglycerols and 1.2% polar lipids. Nuts are cholesterol‐free, but their fatty fraction contains sizeable amounts of chemically related non‐cholesterol sterols, belonging to a heterogeneous group of compounds known as plant sterols or phytosterols.…”
Section: Introductionmentioning
confidence: 99%
“…The highest content of tocopherols found in HNP concentrate ( Table 1 ) could explain a higher content of α-tocopherol and γ-tocopherol in HNP cheese. Di Nunzio [ 38 ] and Lucchetti et al [ 39 ] also found hazelnut peel rich in tocopherols. As expected in dairy products, α-tocopherol was the main isomer of vitamin E in both cheese groups, but the diet also affected α- and γ-tocopherol proportions, in favor of γ-isomer in HNP cheeses.…”
Section: Discussionmentioning
confidence: 99%
“…They constitute over 60% of the kernel dry weight. Among fatty acids, specifically, oleic acid is the predominant one reaching up to 82.8%, followed by linoleic, palmitic, stearic, and vaccenic acids [85][86][87][88]. A high content in monounsaturated fatty acids makes hazelnut oil very much similar to olive oil, mainly contributing to reducing the risk of coronary heart diseases.…”
Section: The Hazelnutmentioning
confidence: 99%